2013
DOI: 10.1016/j.jaci.2012.12.1573
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal bisphenol A exposure and asthma development among inner-city children

Abstract: Background Bisphenol A (BPA) is used widely to manufacture food container linings. Mouse models suggest exposure to BPA might increase allergic inflammation. Objectives We hypothesized that BPA exposure, as assessed based on urinary BPA concentrations, would be associated with increased odds of wheeze and asthma and increased fraction of exhaled nitric oxide (FENO) values in children. Methods The Columbia Center for Children’s Environmental Health recruited pregnant women for a prospective birth cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 57 publications
7
141
2
2
Order By: Relevance
“…A birth cohort study from the mid-west US (Spanier et al, 2012) reported a positive association between maternal urinary Table 5 Birth cohort studies examining the association between prenatal exposure to phthalates, BPA or perfluoroalkyl substances and measures of childhood allergy. Study BPA levels and childhood wheeze whereas the NY birth cohort investigators (Donohue et al, 2013) reported an inverse association. In contrast, in the present study we identified a nonlinear association between BPA and elevated IgE.…”
Section: Prenatal Exposure To Bpa and Measures Of Childhood Allergymentioning
confidence: 94%
“…A birth cohort study from the mid-west US (Spanier et al, 2012) reported a positive association between maternal urinary Table 5 Birth cohort studies examining the association between prenatal exposure to phthalates, BPA or perfluoroalkyl substances and measures of childhood allergy. Study BPA levels and childhood wheeze whereas the NY birth cohort investigators (Donohue et al, 2013) reported an inverse association. In contrast, in the present study we identified a nonlinear association between BPA and elevated IgE.…”
Section: Prenatal Exposure To Bpa and Measures Of Childhood Allergymentioning
confidence: 94%
“…The results indicate that this correlation decreases along with the age of the child. Donohue et al (2013) [106] conducted a study on 568 pregnant women and children 3, 5 and 7 years old. They collected urine samples from women during pregnancy and from children, and additionally, a questionnaire survey on the prevalence of wheeze according to age was performed.…”
Section: Children's Development Birth Weightmentioning
confidence: 99%
“…It was recently demonstrated that prenatal and early-life exposure to bisphenol A (BPA), a xenooestrogen used to manufacture plastics (e.g. for toys and drinking vessels), is associated with an increased risk of wheezing and asthma [67,68]. The phthalates used in numerous plastic consumer products have also attracted attention and there is converging evidence that exposure to di(2-ethylhexyl)phthalate and benzylbutylphthalate during childhood is associated with the development of allergic disease [69].…”
Section: Second-hand Smoke Exposurementioning
confidence: 99%